EVALUASI STRUKTUR GEDUNG FAKULTAS HUKUM UNIVERSITAS MUHAMMADIYAH SUMATERA BARAT - Deddy Kurniawan; Asiya Nurhasanah Habirun; Afif Pratama (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2024)
The Faculty of Law Building of Muhammadiyah University of West Sumatra was established in 1986 and is located in Bukittinggi City, West Sumatra, Indonesia. This building functions as a 2-story lecture building using reinforced concrete structural materials. The building will be added as much as 1 floor above the existing building. In view of this, an inspection and evaluation of the performance of the existing structure was carried out. Research activities include visual inspection, field testing, namely Hammer Test on structural elements, and structural analysis. The capacity of the column structural elements is not able to withstand the load for a 3-story building because the forces acting are outside the interaction diagram. The results of the pushover analysis with the SAP 2000 program for the x-x direction obtained 30 steps and for the y-y direction obtained 18 steps of the thrust load pattern given by the structure until the structure collapses. According to ATC-40, for the calculation of the maximum total deviation is included in the Damage Control (DC) category level and the maximum inelastic deviation is included in the Life Safety (LS) and Structural Stability (SS) category levels, meaning that the building is unable to withstand the earthquake that occurred and the risk of human casualties is very large, so that additional floors cannot be added.Keywords: Inspection, structure capacity, pushover analysis